2018
DOI: 10.1371/journal.pone.0192560
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis of ecosystem service relationships to improve targeting of payments for hydrological services

Abstract: Payment for hydrological services (PHS) are popular tools for conserving ecosystems and their water-related services. However, improving the spatial targeting and impacts of PHS, as well as their ability to foster synergies with other ecosystem services (ES), remain challenging. We aimed at using spatial analyses to evaluate the targeting performance of México’s National PHS program in central Veracruz. We quantified the effectiveness of areas targeted for PHS in actually covering areas of high HS provision an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 97 publications
(284 reference statements)
0
8
0
Order By: Relevance
“…A significant body of literature has been published on this case. Many authors have examined the impacts of PWS programs in the basin through different approaches including technical implementation (Scullion et al, 2011), spatial analyses (Mokondoko et al, 2018), institutional decentralization (Nava-López et al, 2018), social participation (Jones et al, 2019), etc. These works have contributed to significant understanding of the strengths and weaknesses of PWS in the basin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant body of literature has been published on this case. Many authors have examined the impacts of PWS programs in the basin through different approaches including technical implementation (Scullion et al, 2011), spatial analyses (Mokondoko et al, 2018), institutional decentralization (Nava-López et al, 2018), social participation (Jones et al, 2019), etc. These works have contributed to significant understanding of the strengths and weaknesses of PWS in the basin.…”
Section: Resultsmentioning
confidence: 99%
“…Scullion et al (2011) have reported that remote-sensing data show that deforestation was substantially lower on properties receiving PWS payments compared to properties not enrolled in the programs, but the programs did not prevent the net loss of forests within Coatepec. Similarly, Mokondoko et al (2018) utilized spatial analysis to compare the impact of payments for hydrological services on delivery of hydrological services in the basin. The study illustrates that mismatches exist between PWS-targeted areas and geographic areas of priority.…”
Section: Resultsmentioning
confidence: 99%
“…It is especially important to investigate the synergies and tradeoffs of UES in urban and peri-urban areas so the consequence of planning decisions can be considered systematically [92,93]. Although 58% of studies in the region assessed multiple ecosystem services, only 4% dealt with synergies and tradeoffs.…”
Section: Ii)mentioning
confidence: 99%
“…bringing into question the additionality of such programs. Adding to efficacy concerns, studies have shown that PHS programs are often lacking in areas identified as priority areas for hydrological service provisioning (Mokondoko et al 2018). Recent work (Costedoat et al 2015;Berry et al In review) suggests that hydrologic metrics, such as measures of dry-season streamflows, can be valuable indicators of ecosystems services provided by forests and converted land uses.…”
Section: Incorporating Citizen Science Into Hydrological Models To Bementioning
confidence: 99%
“…Although CONAFOR publishes a detailed explanation of the methodology used to select eligible zones in target watersheds that can receive payments, no guidance is provided to prioritize where the payments should be targeted within these zones. Targeting criteria are typically assigned by local PHS program operators using a mix of spatially explicit biophysical and socio-economic data, such as a combination of deforestation risk and degree of socioeconomic marginalization (Mokondoko et al 2018;Von Thaden et al 2019). According to interviews with local program operators, they do not consider spatially explicit hydrological information, such as locations where the greatest amount of groundwater recharge occurs, in their targeting methodologies.…”
mentioning
confidence: 99%